2020
DOI: 10.3389/fncel.2020.605312
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation of CaV3.2 Channels Contributes to the Hyperalgesia in Peripheral Neuropathy of Type 1 Diabetes

Abstract: Our previous studies implicated glycosylation of the CaV3.2 isoform of T-type Ca2+ channels (T-channels) in the development of Type 2 painful peripheral diabetic neuropathy (PDN). Here we investigated biophysical mechanisms underlying the modulation of recombinant CaV3.2 channel by de-glycosylation enzymes such as neuraminidase (NEU) and PNGase-F (PNG), as well as their behavioral and biochemical effects in painful PDN Type 1. In our in vitro study we used whole-cell recordings of current-voltage relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Here, we specifically focused on punctate mechanical hyperalgesia and spontaneous pain measures, given that they are the most relevant to clinical setting [ 36–38 ]. We have previously established that Ca V 3.2 channels play an important role in the development of both thermal and mechanical hyperalgesia in the incisional pain model in rats and mice [ 19 , 20 , 26 ]. We also demonstrated that hyperalgesia develops to a lesser extent in Ca V 3.2 knock-out (KO) mice as compared to WT mice [ 20 ], and that T-channel blockers can successfully alleviate both thermal and mechanical hyperalgesia after surgical incision in rats [ 19 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we specifically focused on punctate mechanical hyperalgesia and spontaneous pain measures, given that they are the most relevant to clinical setting [ 36–38 ]. We have previously established that Ca V 3.2 channels play an important role in the development of both thermal and mechanical hyperalgesia in the incisional pain model in rats and mice [ 19 , 20 , 26 ]. We also demonstrated that hyperalgesia develops to a lesser extent in Ca V 3.2 knock-out (KO) mice as compared to WT mice [ 20 ], and that T-channel blockers can successfully alleviate both thermal and mechanical hyperalgesia after surgical incision in rats [ 19 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously established that Ca V 3.2 channels play an important role in the development of both thermal and mechanical hyperalgesia in the incisional pain model in rats and mice [ 19 , 20 , 26 ]. We also demonstrated that hyperalgesia develops to a lesser extent in Ca V 3.2 knock-out (KO) mice as compared to WT mice [ 20 ], and that T-channel blockers can successfully alleviate both thermal and mechanical hyperalgesia after surgical incision in rats [ 19 , 20 , 26 ]. Our earlier study [ 25 ] demonstrated that ALA reduced T-currents in freshly dissociated cell bodies of sensory neurons in dorsal root ganglia of rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective in vivo knock-down of the Ca V 3.2 isoform of T-channels in DRG neurons reduced both hyperalgesia in vivo , and T-currents in dissociated DRG neurons of small diameter in vitro , suggesting a correlation between hyperglycemia and increased T-currents with the appearance of mechanical and thermal sensitivity in diabetic STZ-treated rats ( 59 , 61 ). In vivo application of glycosylation inhibitors, such as NEU both peripherally and centrally, ameliorated hyperalgesia in a model of type I diabetes in rodents, except in Ca V 3.2 knock-out mice ( 62 ). Similarly, recent study by ( 63 ) revealed that NEU exhibits desensitizing effects in terms of spontaneous activity and stimulated release of CGRP (calcitonin gene related peptide).…”
Section: The Role Of T-channels In Painful Pdnmentioning
confidence: 99%
“…However, further investigations focusing on the net forward trafficking of Ca V 3.2 will be needed to ascertain a role of N-glycosylation of Ca V 3.2 on its recycling or forward trafficking. As Ca V 3.2 channel up-regulation is a common feature in the development and maintenance of multiple pain processes [ 48 ], and alterations of Ca V 3.2 channels glycosylation have been associated with the development of pain related to diabetes [ 43 , 45 , 49 ], understanding Ca V 3.2 trafficking and the impact of its glycosylation are of significant therapeutic relevance [ 50 ].…”
Section: Forward Trafficking Of Ca V : From Er Tomentioning
confidence: 99%